Pengaruh substitusi terigu dengan kacang tunggak (Vigna unguiculata L.) dan ikan gabus (Channa striata) terhadap elastisitas dan warna MP-ASI mie basah: The effect of wheat substitution with cowpeas (Vigna unguiculata L.) and snakehead fish (Channa striata) on the elasticity and color of wet noodles Complementary Feeding - Nur Adistiya, Tiara; Aprilia, Veriani; Ariftiyana, Siska (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Optimal growth and development in the first thousand days of life (1000 HPK) can be achieved by starting complementary feeding (CF) for infants aged 6-23 months to fulfill nutritional needs and prevent nutritional disorders such as stunting. CF noodle products with local food substitutions are cowpea and snakehead fish which are high in protein, soft textured, and without chemical additives for children aged 12-23 months. This study aimed to determine the effect of wheat substitution with cowpea and snakehead fish on the physical properties (water absorption, elasticity, color) in wet noodle CF. This research used a completely randomized design (CRD) with 4 treatments namely F0 (0%), F1 (20%), F2 (40%), F3 (60%). The parameters analyzed included physical properties of water absorption, elasticity, and color properties (L, a, b). Data were analyzed using One Way ANOVA test and Duncan's Multiple Range Test (DMRT) to know the differences in all samples. Statistical test results indicated a significant effect of substituting wheat with cowpea on elasticity and color (L*, a*, b*). The more composite flour added, the elasticity of the wet noodles decreased, and the L* (brightness) tended to be darker, the a* (redness) greener, and the b* (yellowness) yellower. Meanwhile, there was no significant effect on the water absorption of wet noodle CF. Increased substitution of cowpea and snakehead fish flour affected elasticity and color (L* darker, a* greener, b* yellower), although there was no significant effect on the water absorption of wet noodles.